10
$\begingroup$

Question: Can we show that $$\phi=\frac{1}{2}+\frac{11}{2}\sum_{n=0}^\infty\frac{(2n)!}{5^{3n+1}(n!)^2} $$; where $\phi={1+\sqrt{5} \above 1.5pt 2}$ is the golden ratio ?


Some background and motivation:

Wikipedia only provides one series for the golden ratio - see also the link in the comment by @Zacky. I became curious if I could construct another series for the Golden Ratio based on a slight modification to a known series representation of the $\sqrt{2}.$ At first I considered $$\sqrt{2}=\sum_{n=0}^\infty(-1)^{n+1}\frac{(2n+1)!!}{(2n)!!}$$; which series can be accelerated via an Euler transform to yield $$\sqrt{2}=\sum_{n=0}^\infty(-1)^{n+1}\frac{(2n+1)!!}{2^{3n+1}(n!)^2}$$ This last series became the impetus to try and and get to the Golden ratio. Through trial and error I stumbled upon $$\frac{\sqrt{5}}{11}=\sum_{n=0}^\infty\frac{(2n)!}{5^{3n+1}(n!)^2}$$

$\endgroup$
  • 13
    $\begingroup$ $$\sum_{n\geq 0}\frac{\binom{2n}{n}}{4^n}x^{n} = \frac{1}{\sqrt{1-x}}$$ (for $-1\leq x < 1$) is everything you need. $\endgroup$ – Jack D'Aurizio Dec 30 '18 at 14:59
  • 1
    $\begingroup$ I am pretty sure I have seen this before on MSE. It was a post that asked if this series is true and it was painted on something like a poster, or on a book. $\endgroup$ – Zacky Dec 30 '18 at 15:20
  • 2
    $\begingroup$ Fully solved here. $\endgroup$ – Did Dec 30 '18 at 20:48
  • 2
    $\begingroup$ @AntonioHernandezMaquivar "Any reason why this question is being voted to [be] close[d?]" The first reason that springs to mind is the total lack of personal input, which one may find all the more surprising coming from an OP member for 3+ years and with 100+ questions asked. $\endgroup$ – Did Dec 30 '18 at 20:52
  • 1
    $\begingroup$ @upvoters Any reason why this question is being upvoted? Apparently 8 users believe the question respects the etiquette of the site? Please explain. $\endgroup$ – Did Dec 30 '18 at 20:54
21
$\begingroup$

First of all note that

$$\frac1{\sqrt{1-4x}}=\sum_{n=0}^{\infty}\binom{2n}n x^n$$

Lets rewrite your sum as the following

$$\sum_{n=0}^\infty\frac{(2n)!}{5^{3n+1}(n!)^2}=\frac15\sum_{n=0}^\infty\binom{2n}n\left(\frac1{5^3}\right)^n=\frac15\frac1{\sqrt{1-\left(\frac4{5^3}\right)}}=\frac{\sqrt 5}{11}$$

And therefore you can correctly conclude that

$$\frac{1}{2}+\frac{11}{2}\sum_{n=0}^\infty\frac{(2n)!}{5^{3n+1}(n!)^2}=\frac12+\frac{11}2\frac{\sqrt 5}{11}=\frac{1+\sqrt 5}2$$

$$\therefore~\frac{1}{2}+\frac{11}{2}\sum_{n=0}^\infty\frac{(2n)!}{5^{3n+1}(n!)^2}=\phi$$

$\endgroup$
  • 1
    $\begingroup$ What is the motivation behind: $\frac1{\sqrt{1-4x}}=\sum_{n=0}^{\infty}\binom{2n}n x^n $ ? $\endgroup$ – Antonio Hernandez Maquivar Dec 30 '18 at 15:11
  • 1
    $\begingroup$ Why should I have thought of $\frac1{\sqrt{1-4x}}=\sum_{n=0}^{\infty}\binom{2n}n x^n$ as a starting point to prove my own series ? $\endgroup$ – Antonio Hernandez Maquivar Dec 30 '18 at 15:16
  • 2
    $\begingroup$ @AntonioHernandezMaquivar: $$\frac{d^n}{dx^n}\left.\left(\frac{1}{\sqrt{1-x}}\right)\right|_{x=0}$$ is straightforward to compute by induction or by invoking the extended binomial theorem. $\endgroup$ – Jack D'Aurizio Dec 30 '18 at 15:17
  • 2
    $\begingroup$ @AntonioHernandezMaquivar Since $\frac{(2n)!}{(n!)^2}=\binom{2n}n$ which is called the central binomial coefficient. This one is used quite often for the purpose of expressing series expansions of well-know functions such as the $\arcsin$ or square root function. Thus, seeing this structure within a given series implies a possible connection to one of these functions which I conjectured and it turned out that the series expansion of the function $\frac1{\sqrt{1-4x}}$ is a good choice in this situtation. $\endgroup$ – mrtaurho Dec 30 '18 at 15:28
  • 2
    $\begingroup$ You get $(1-4x)^{-1/2}=\sum_{k=0}^\infty\binom{-1/2}{k}(-4x)^k$, which is the general binomial series for $|4x|<1$. Then explore $$\binom{-1/2}{k}=\frac{(-1/2)(-1/2-1)...(-1/2-k+1)}{k!}=(-1/2)^k\frac{(2k-1)(2k-3)...3\cdot 1}{k!}=(-1/4)^k\frac{(2k)!}{(k!)^2}.$$ $\endgroup$ – LutzL Dec 31 '18 at 11:15
5
$\begingroup$

Using Calculating $1+\frac13+\frac{1\cdot3}{3\cdot6}+\frac{1\cdot3\cdot5}{3\cdot6\cdot9}+\frac{1\cdot3\cdot5\cdot7}{3\cdot6\cdot9\cdot12}+\dots? $,

$$\dfrac{(2n)!}{5^{3n+1}(n!)^2}=\dfrac{2^n\cdot1\cdot3\cdot5\cdots(2n-3)(2n-1)}{5^{3n+1}n!}=\dfrac{-\dfrac12\left(-\dfrac12-1\right)\cdots\left(-\dfrac12-(n-1)\right)}{n!\cdot5}\left(-\dfrac4{5^3}\right)^n$$

$$\implies5\sum_{n=0}^\infty\dfrac{(2n)!}{5^{3n+1}(n!)^2}=\left(1-\dfrac4{5^3}\right)^{-1/2}=?$$

Alternatively using Calculating $1+\frac13+\frac{1\cdot3}{3\cdot6}+\frac{1\cdot3\cdot5}{3\cdot6\cdot9}+\frac{1\cdot3\cdot5\cdot7}{3\cdot6\cdot9\cdot12}+\dots? $,

Using Generalized Binomial Expansion, $$(1+x)^m=1+mx+\frac{m(m-1)}{2!}x^2+\frac{m(m-1)(m-2)}{3!}x^3+\cdots$$ given the converge holds

$mx=\dfrac{2!}{5^3(1!)^2},\dfrac{m(m-1)}2x^2=\dfrac{4!}{5^6(2!)^2}$

$\implies m=-\dfrac12,x=-\dfrac4{5^3}$

$\endgroup$
4
$\begingroup$

We know that the approximates by partial continued fractions of the golden ratios are the quotients of successive Fibonacci numbers $1,1,2,3,5,8,13,...$. Taking $$ \phi=\frac{1+\sqrt{5}}2\approx \frac{8}5\implies \sqrt5\approx \frac{11}{5} $$ we get a lower approximation for $\sqrt5$. To the remainder of the square root after factoring out the approximation we can apply the the Newton/binomial series for the inverse square root $$ \sqrt5=\frac{11}{5}\sqrt{\frac{125}{121}}=\frac{11}{5}\left(1-4\frac1{5^3}\right)^{-1/2} =\frac{11}5\sum_{n=0}^\infty\binom{2n}{n}\frac1{5^{3n}} $$ which is the series you got.


Exploring the same method for one place further in the Fibonacci sequence $$ \phi=\frac{1+\sqrt{5}}2\approx \frac{13}8\implies \sqrt5\approx \frac{9}{4} $$ gives an upper approximation of $\sqrt5$ and thus an alternating series, $$ \sqrt5=\frac{9}{4}\sqrt{\frac{80}{81}}=\frac{9}{4}\left(1+4\frac1{320}\right)^{-1/2} =\frac{9}4\sum_{n=0}^\infty\binom{2n}{n}\frac{(-1)^n}{320^{n}} $$


Why that series?

The general binomial series reads as $$(1+x)^α=\sum_{n=0}^\infty\binom{α}n.$$ For $α=-1/2$ the binomial coefficient can be transformed as $$ \binom{-1/2}{n}=\frac{(-1/2)(-1/2-1)...(-1/2-n+1)}{n!}=(-1/2)^n\frac{(2n-1)(2n-3)...3\cdot 1}{n!}=(-1/4)^n\frac{(2n)!}{(n!)^2}, $$ resulting in the "simplified" formula $$\frac1{\sqrt{1-4x}}=\sum_{n=0}^\infty\binom{2n}nx^n.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.